PENGEMBANGAN MEDIA E-MODUL INTERAKTIF BERBASIS WEB GOOGLE SITES PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Adfha Putri Tony; Yeni Erita; Zuardi; Desyandri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the problem of suboptimal use of learning media in elementary schools and the lack of development of interactive e-modules based on Google Sites for IPAS (Social Studies) learning at the elementary school level. Although learning media such as videos have been used, these have not been effective in helping students understand the lesson material. Additionally, conventional media such as printed materials still dominate, even though the school’s facilities are adequate. As a result, students appear bored, uninterested, and passive in their learning. The purpose of this study is to develop a valid, practical, and effective interactive e-module media based on Google Sites for IPAS learning in elementary schools. This research is a Research and Development (R&D) study using the ADDIE model. The research findings show that the interactive e-module media based on Google Sites is highly valid, with scores of 98.46% (content), 92% (language), and 91.67% (media), resulting in an average validity score of 94.04%. The practicality test results indicate that the media is highly practical, with scores of 97.14% (teacher) and 93.54% (students) at SDN 19 Kampung Olo, 97.14% (teacher) and 94.07% (students) at SDN 05 Surau Gadang, and 97.14% (teacher) and 97.5% (students) at SDN 08 Surau Gadang. The effectiveness test results show that the media is highly effective, with N-Gain scores of 91.83% (high) at SDN 19 Kampung Olo, 96.25% (high) at SDN 05 Surau Gadang, and 92.29% (high) at SDN 08 Surau Gadang. Therefore, the interactive e-module media based on Google Sites is valid, practical, and effective for use in IPAS learning in elementary schools.